Natural Treatment Systems as Sustainable Ecotechnologies for the Developing Countries. (26th June 2013) - Mahmood, Qaisar; Pervez, Arshid; Zeb, Bibi Saima; Zaffar, Habiba; Yaqoob, Hajra; Waseem, Muhammad; Zahidullah,; Afsheen, Sumera
Abstract : The purpose of natural treatment systems is the re-establishment of disturbed ecosystems and their sustainability for benefits to human and nature. The working of natural treatment systems on ecological principles and their sustainability in terms of low cost, low energy consumption, and low mechanical technology is highly desirable. The current review presents pros and cons of the natural treatment systems, their performance, and recent developments to use them in the treatment of various types of wastewaters. Fast population growth and economic pressure in some developing countries compel the implementation of principles of natural treatment to protect natural environment. The employment of these principles for waste treatment not only helps in environmental cleanup but also conserves biological communities. The systems particularly suit developing countries of the world. We reviewed information on constructed wetlands, vermicomposting, role of mangroves, land treatment systems, soil-aquifer treatment, and finally aquatic systems for waste treatment. Economic cost and energy requirements to operate various kinds of natural treatment systems were also reviewed.